Розвиток римо-католицької церкви в Одесі у ХІХ ст. (на матеріалах Державного архіву Одеської Області) - Діанова, Н. (Чорноморська минувшина, 2016)
Мета поданої наукової статті полягає в тому, щоб на основі документів Держархіву Одеської області простежити основні етапи розвитку римо-католицької церкви в Одесі упродовж ХІХ ст. Для досягнення зазначеної мети передбачено комбіноване використання різних наукових методів дослідження, зокрема, евристичного, аналізу і синтезу, класифікації та періодизації, статистичного та ін. In article documentary materials of the state archive of Odessa region which give the chance to consider the main stages of development of the roman catholic church in Odessa during xix century are analyzed. Prerequisites of church construction in the city are investigated. Process of gradual strengthening of positions of the roman catholic church in Odessa is considered. Emphasized that the most successful for the development of catholicism in the city was the period from the late XVIII century to the 20 years of xix century. Its characteristic feature was loyalty to the catholics by local authorities. This is confirmed by the position of the governor-general of Novorossiysk territory and mayor of Odessa, de Richelieu in relation to the roman catholic parishes in the region, which allowed the jesuits. The first visitor of the roman catholic churches in the Novorossiysk region was the jesuit abbé Dominique-Charles Nicholl, who oversaw the activities of all catholic parishes, which were at that time in Kherson, Odessa, Mykolaiv and Severynivk. Цель представленной научной статьи заключается в исследовании основных этапов развития римо-католической церкви в Одессе в течении ХІХ в. на основе документов Государственного архива Одесской области. Для достижения поставленной цели использованы различные научные методы исследования, в частности: эвристический, анализа и синтеза, классификации и периодизации, статистический и др.